Robust Switched Control Design for Nonlinear Systems Using Fuzzy Models - Souza, Wallysonn Alves de; Minhoto Teixeira, Marcelo Carvalho [UNESP]; Alves Santim, Mira Peres; Cardim, Rodrigo [UNESP]; Assunao, Edvaldo [UNESP] (Hindawi Publishing Corporation, 2014)
The paper proposes a new switched control design method for some classes of uncertain nonlinear plants described by Takagi-Sugeno fuzzy models. This method uses a quadratic Lyapunov function to design the feedback controller gains based on linear matrix inequalities (LMIs). The controller gain is chosen by a switching law that returns the smallest value of the time derivative of the Lyapunov function. The proposed methodology eliminates the need to find the membership function expressions to implement the control laws. The control designs of a ball-and-beam system and of a magnetic levitator illustrate the procedure.